Biosynthesis and Characterization of Silver Nanoparticles Using Cacao (Theobroma cacao L) Skin Extract - Irham Pratama Ridwan (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Synthesis of silver nanoparticles has been successfully carried out using extracts of cocoa pod (Theobroma cacao L). Silver nanoparticles were synthesized using the green synthesis method. Biosynthesis was carried out by mixing 1 mM 40 ml AgNO3 solution with 0.5 ml of cocoa pod husk extract, stirring for 1 minute, after a few minutes the solution will change color from yellowish to dark colored, the color change that occurs shows the ion reduction process so that silver nanoparticles are formed. When silver nanoparticles are formed, the UV-Vis absorption spectrum is at a wavelength between 400-500 nm. Characterization and stability using a UV-Vis spectrophotometer with a time variation of 4 hours, 24 hours, 3 days and 7 days of reduction time. With increasing time the resulting long wave gets higher and bigger the size of the aggregation. Sample (1) shows 446, 446, 446, 447.5 nm, obtained a maximum wavelength of 447.5 nm, repeated repetition is labeled sample (2) shows 447, 446.5, 450, 449.5 nm with a maximum wavelength of 495 , 5 nm seen from the wavelength value tends to be stable so there is no need to add a stabilizing agent. The absorbance value increases with time, the greater the absorbance value, the more nanoparticles formed